Integrated methylome and transcriptome analysis of esophageal squamous cell carcinoma in the South African cohort - Moodley, Mishalan (University of the Witwatersrand, Johannesburg, 2024)
Esophageal squamous cell carcinoma is highly prevalent in Eastern and Southern Africa, characterized by a high incidence and mortality. The etiology of Esophageal Squamous Cell Carcinoma is complex, and multiomic studies to improve our understanding of this deadly disease is severely lacking in this part of the world. DNA methylation is an epigenetic mechanism which plays an important role for gene regulation and frequently displays aberrant patterns in several cancers. This study aimed to identify aberrant methylation patterns in Black South African ESCC patients from matched tumour normal pairs. We designed an efficient workflow for the collection, storage, and processing of high quality ESCC specimens ensuring preservation of tissue architecture and sample quality. A total of 142 ESCC samples were collected. Methylome and transcriptome was investigated in 11 paired tumour and adjacent normal ESCC cases. Differential methylation analysis revealed significant alterations in CpG methylation across the genome. Principal component analysis effectively discriminated the tumour samples from adjacent normal tissues for most samples. The focus was on differentially methylated regions within enhancers and promoters using a methylation difference of ≥20% and an expression fold change difference of ≥2 (p values ≤0.05) between tumour and normal tissue. We identified three critical gene promoters (CDC42EP3, TNC and KRT13) and 1 enhancer (COL6A3) that exhibited significant differential methylation and a significant inverse relationship with gene expression, all of which plays a role in the ECM. From transcriptome data, there were 241 identified differentially expressed genes, of which 170 were upregulated and 71 genes that were downregulated and whose gene promoters were and hypomethylated and hypermethylated respectively. The top three candidate genes exhibited an 8-9-fold increase in expression and had the most significant FDR (<10-9 to 10-16), and are are all involved in the ECM pathway: FN1, POSTN and COL6A3. Transcription data also showed that FN1 and POSTN were also among the top 2 differentially expressed genes across all genes, with COL6A3 also making up the top 3 differentially expressed genes. v In summary this study sheds light on the methylome and gene expression changes in ESCC biased towards the ECM and highlights the importance of epigenetic modifications and their potential role in the disease. Understanding these molecular alterations is critical for developing targeted therapeutic strategies for ESCC.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Esophageal squamous cell carcinoma (ESCC); Methylation; ranscriptome; SDG-3: Good health and well-being